Treatment arterial primary hypertension - Iza Stoll, Agustín (2006)
Arterial hypertension is related to increased cardiovascular, cerebrovascular, and renal disease risk. Early identification and intervention in pre hypertensive patients through life style modification could prevent hypertension and related outcomes. Pre hypertension subjects have increase probability of suffering cardiovascular events compared to normal blood pressure individuals. In the current symposium paper we try to give an integral vision of primary arterial hypertension treatment.